The Effect of Export Assistance Program Usage on Export Performance: A Contingency Explanation - Gençtürk, Esra F.; Kotabe, Masaaki (Journal of international marketing (East Lansing, Mich.), 2001)
On the basis of a synthesis of prior research, the authors develop a model, which integrates export marketing involvement and the use of government export promotion assistance programs as critical variables affecting export performance, and subject it to empirical evaluation. In this context, the authors also investigate organizational and managerial differences among the firms involved in export marketing to ascertain the robustness of and replicate the observed differences in firms' export marketing involvement behavior. The results indicate that export marketing involvement of firms and firms' usage of government export assistance programs are important export success factors. However, the relevance of export assistance programs and the role they play vary depending on the dimension of export performance being considered.